Masraf al-Zakat “Fi SabilillahTasawwuran wa Atharan Fi al-Tanmiyyat al-Ijtima’iyyah wa al-Iqtisadiyyah - Mahadi, Mohammad; Daud, Ismail; Wan Mohd Khairul Firdaus, Wan Khairuldin; Asyraf, Abdul Rahman (2018)
Asnaf Fi Sabilillah is among the recipients of zakat. This Asnaf has an important role in social development. However, in most Islamic countries, it is realized in a narrow and limited scope only to the aspect of jihad and education, regardless of the wider social interests and welfare of the Muslim countries today. This study aims to explain concepts, distributions and the impact of Asnaf Fi Sabilillah in the process of contemporary social transformation. The study uses a content analysis approach by adapting descriptive-deductive method. The findings show that Asnaf Fi Sabilillah should be applied in the broader meaning of jihad covering all activities that contribute to the development of da'wah for the sake of Allah, if there is no specific fund from a particular party. Asnaf Fi Sabilillah which is managed more effectively is part of revitalizing the country's economy and thus improving its status for social progress. However, its implementation needs to be in line with Shariah law to avoid corrupt governance in the Muslim world.